2013
DOI: 10.2967/jnumed.113.121897
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Detection of Monoaminergic Degeneration in Early Parkinson Disease by 18F-9-Fluoropropyl-(+)-Dihydrotetrabenzazine PET

Abstract: PET with 18 F-9-fluoropropyl-(1)-dihydrotetrabenzazine ( 18 F-DTBZ), a novel radiotracer targeting vesicular monoamine transporter type 2 (VMAT2), has been proven as a useful imaging marker to measure dopaminergic integrity. Methods: The aim of this study was to evaluate the capability of 18 F-DTBZ PET in detecting the monoaminergic degeneration in early Parkinson disease (PD) in vivo. Seventeen age-matched healthy subjects and 30 PD patients at early stage of disease (duration of disease # 5 y) with mild and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 45 publications
(83 reference statements)
2
31
0
Order By: Relevance
“…As stated in [13], positron emission tomography (PET) scans of human brains could help in detecting Parkinson's Disease (PD) at an earlier stage. PET is a nuclear medicine, functional imaging technique, which detects the amount of radioactive substance (called radionuclide or radioactive tracer) that is injected into the subject in order to construct a three-dimensional image for further examination of the tissue under study.…”
Section: Case Studymentioning
confidence: 99%
See 2 more Smart Citations
“…As stated in [13], positron emission tomography (PET) scans of human brains could help in detecting Parkinson's Disease (PD) at an earlier stage. PET is a nuclear medicine, functional imaging technique, which detects the amount of radioactive substance (called radionuclide or radioactive tracer) that is injected into the subject in order to construct a three-dimensional image for further examination of the tissue under study.…”
Section: Case Studymentioning
confidence: 99%
“…PET is a nuclear medicine, functional imaging technique, which detects the amount of radioactive substance (called radionuclide or radioactive tracer) that is injected into the subject in order to construct a three-dimensional image for further examination of the tissue under study. It was addressed in [13] that by analyzing the reduction of the vesicular monoamine transporter 2 (VMAT2) density from the PET image, PD can be diagnosed effectively. VMAT2 is a specific presynaptic protein involved in the transport of monoamines from cytosol to storage vesicles of monoaminergic nerve terminals.…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that novel neuroimaging tools could aid in the early diagnosis and monitoring of PD such as [ 18 F]DTBZ PET, a vesicular monoamine transporter 2 (VMAT-2) marker, for measuring dopaminergic terminal loss [5,6]. Semi-automated measurement of substantia nigra pars compacta (SNc) volume with 3D-neuromelanin sensitive MRI has been demonstrated to be able to distinguish PD patients from healthy subjects (HS), especially in the early stage of the disease [7].…”
Section: Movement Disordersmentioning
confidence: 99%
“…Parkinson's disease (PD) is the second most prevalent neurodegenerative disorder in the elderly population, following Alzheimer's disease (Lin et al, 2014). PD is a chronic disorder, characterized primarily by motor deficits including resting tremor, rigidity, bradykinesia, and postural instability (Burke & O'Malley, 2013;Choi et al, 2016;Lohr & Miller, 2014;Miller et al, 1999;Taylor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%